2011
DOI: 10.1088/0964-1726/20/4/043001
|View full text |Cite
|
Sign up to set email alerts
|

A review of magnetostrictive iron–gallium alloys

Abstract: A unique combination of low hysteresis, moderate magnetostriction at low magnetic fields, good tensile strength, machinability and recent progress in commercially viable methods of processing iron-gallium alloys make them well poised for actuator and sensing applications. This review starts with a brief historical note on the early developments of magnetostrictive materials and moves to the recent work on FeGa alloys and their useful properties. This is followed by sections addressing the challenges specific t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
177
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 336 publications
(190 citation statements)
references
References 90 publications
9
177
1
3
Order By: Relevance
“…We study a film of Galfenol, which is a novel ferromagnetic alloy of Iron and Gallium of high technological potential [20,21]. The combination of enhanced magnetostriction, high saturation magnetization of 1.8 T and low saturation field with technological accessibility makes Galfenol attractive for nanoscale magnetostrictive applications [21], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We study a film of Galfenol, which is a novel ferromagnetic alloy of Iron and Gallium of high technological potential [20,21]. The combination of enhanced magnetostriction, high saturation magnetization of 1.8 T and low saturation field with technological accessibility makes Galfenol attractive for nanoscale magnetostrictive applications [21], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Its outstanding mechanical and magnetic properties make it a promising candidate for different applications. 28 Here, we demonstrated that the stability of magnetic state of FeGa nanodots is not only a function of lateral dimensions, but also sensitive to interfacial coupling strain controlled by the magnitude and direction of the external electric field. Moreover, we systematically revealed how various transformation paths of magnetic states including those between states with different orders (i.e., one is polar and the other is vortex), and those between states with the same order (i.e., both are polar or both are vortex) can be electrically induced as schematically illustrated in Fig.…”
Section: Introductionmentioning
confidence: 80%
“…1) Thus, the application of Fe-Ga alloys to actuator devices have actively investigated. In addition, the inverse effect of magnetostriction of Fe-Ga alloys has also attracted much attention for application to energy harvesting technology, which can generate electrical power from ambient vibration.…”
Section: Introductionmentioning
confidence: 99%